Social network analysis with applications - McCulloh, Ian; Armstrong, Helen (Helen Leslie); Johnson, Anthony N. (John Wiley & Sons, Inc., 2013)
Authored by military and intelligence professionals, this book introduces the new and emerging topic of social network analysis. Focusing on models and methods for the analysis of organizational risk, the book provides easily accessible yet comprehensive coverage of networks basics, basic centrality measures, social links, subgroup analysis, data sources, and more. Examples of mathematical calculations and formulas for social network measures are also included.